2016
DOI: 10.1111/jcc4.12176
|View full text |Cite
|
Sign up to set email alerts
|

Differential Use, Differential Effects: Investigating the Roles of Different Modes of News Use in Promoting Political Participation

Abstract: The present study clarifies the role of the informational use of media in facilitating citizens' political participation by focusing on three distinctive modes of news experience (i.e., news reading, posting, and endorsing)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
1
17
0
2
Order By: Relevance
“…Scholarly understanding of news sharing, a more esoteric behavior, had less to gain from this approach. The findings here conform with past studies in suggesting that sharing is mostly accomplished by more avid and politically involved SM users and that it is linked to political participation (Choi, 2016a;Kalogeropoulos et al, 2017;Kumpel et al, 2015;Weeks and Holbert, 2013). Nevertheless, the present analysis did advance theoretical understanding regarding SM news viewing.…”
Section: Discussionsupporting
confidence: 91%
“…Scholarly understanding of news sharing, a more esoteric behavior, had less to gain from this approach. The findings here conform with past studies in suggesting that sharing is mostly accomplished by more avid and politically involved SM users and that it is linked to political participation (Choi, 2016a;Kalogeropoulos et al, 2017;Kumpel et al, 2015;Weeks and Holbert, 2013). Nevertheless, the present analysis did advance theoretical understanding regarding SM news viewing.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, Freeman (2013) concludes that the Internet is the main source of news among young people and, although the online press is their first choice for consultation, they prefer to play the role of active audiences in media and social networks to share their own comments. In this regard, Choi (2016) also argues that the publication of news on social networks contributes to young people's participation and Guerrero (2018) claims that young people are moving away from television to never come back. Similarly, Gil de Zúñiga et al (2016) have concluded that one of the reasons that promotes the use of social networks is the need to engage in debates on certain public affairs, as well as the need to get news to share their opinions and to find support in their surroundings.…”
Section: News Consumptionmentioning
confidence: 99%
“…Future studies would also benefit from more contextually specific measures of social media news engagement rather than the generic measures used in the present study, which may have contributed to the marginal Cronbach's alpha score. Past studies strongly suggest that different uses of the Internet often lead to different outcomes (Choi 2016). For example, "commenting" on news posts often require more cognitive effort compared with just "sharing" them.…”
Section: Limitations and Conclusionmentioning
confidence: 99%